Informal enterprise incubation in newly established informal settlements and its interaction with regulatory urban planning practice and retail by-laws: The case of Azania settlement in Kayamandi, Stellenbosch - Sithole, Sithuthuke Khwezi (Stellenbosch : Stellenbosch University, 2026)
Thesis (MPhil)--Stellenbosch University, 2025.